Organocatalytic and metal-mediated asymmetric [3+2] cycloaddition reactions - Xing, Yalan; Wang, Nai-Xing (Coordination chemistry reviews, 2012)
► 1,3-Dipolar reactions subject to both concerted reaction mechanism and the stepwise mechanism. ► Click chemistry is not a concerted 1,3-dipolar cycloaddition but a stepwise copper(I)-catalyzed process. ► Theoretical aspects and synthetic applications of these organocatalytic and metal-mediated asymmetric [3+2] cycloadditions are summarized. ► FMO theory to the reactivity of concerted 1,3-dipolar cycloadditions is reviewed. This review focuses on recent progress in organocatalytic and metal-mediated asymmetric [3+2] cycloadditions, including ‘click’ chemistry, asymmetric 1,3-dipolar and asymmetric non-1,3-dipolar [3+2] cycloadditions. The theoretical aspects and synthetic applications of these organocatalytic and metal-mediated asymmetric [3+2] cycloadditions are summarized. In addition, an understanding of the mechanistic details which lead to efficient stereoselectivity in organocatalytic and metal-mediated asymmetric [3+2] cycloadditions is provided. Most of the references reviewed in this paper are from 2007 upto now.